From Coffee To Data: The Influence Of Cardano On Ethiopia’s Coffee Trade - Rizki Puji Gustian (Dinasti International Journal of Education Management And Social Science, 2024)
Ethiopia's primary export, coffee, has been instrumental in its economic growth. A blockchain multinational company named Cardano advocated for the adoption of their technology in Ethiopia. However, instead of fostering development, the push for blockchain by developed nations perpetuates structural imperialism. This stems from disparities in economic distribution and ICT knowledge. This study examines Cardano's influence on Ethiopia's coffee sector in 2018, revealing a dynamic where developed countries exert influence over developing ones. Cardano's technological prowess positions it at the center, impacting Ethiopia as a peripheral player in blockchain adoption for coffee trade enhancement. Despite Ethiopia's coffee exports tripling in value, the collaboration also benefits Cardano, leading to unequal labor division and economic gains. Furthermore, Cardano's initiatives spawn additional blockchain applications, extending its influence across various sectors.